An Enhanced Red-Based Weighted Fair Priority Queuing Algorithm For Ieee 802.16 Subscriber Station Scheduler - Kasaci, Serda; Oktug, Sema (Aperta, 2010)
IEEE 802.16, which is called as Worldwide Interoperability for Microwave Access (WiMAX), is an air interface for Fixed Broadband Wireless Access Systems. In the 802.16 IEEE standard, different service types are introduced, such as Unsolicited Grant Service (UGS), Real-time Polling Service (rtPS), Non-Real-time Polling Service (nrtPS) and Best Effort (BE). Each service type is associated with a set of Quality of Service (QoS) parameters; however WiMAX does not specify how to schedule the granted bandwidth efficiently between these service classes. In this paper, we propose an Enhanced RED-based Weighted Fair Priority Queuing algorithm for Subscriber Stations. The weights are calculated according to the traffic load of the rtPS and nrtPS service classes. Simulation results show that, both rtPS and nrtPS throughputs are improved without starving lower priority service classes.